Redescription of Cheilinus quinquecinctus Rüppell, 1835 (Pisces: Perciformes, Labridae), a valid endemic Red Sea wrasse - Bogorodsky, Sergey V.; Alpermann, Tilman J.; Mal, Ahmad O. (Zootaxa, 2016)
The labrid fish Cheilinus quinquecinctus Rüppell, originally described from the Red Sea, has long been regarded as a junior synonym of C. fasciatus (Bloch). Herein, both nominal species are redescribed, based on examination of the types and additional material from the Red Sea (for C. quinquecinctus) and the Indo-West Pacific (for C. fasciatus). Rüppell's description of Cheilinus quinquecinctus was originally based on three syntypes, and the most representative adult specimen is designated as the lectotype. We show that Cheilinus quinquecinctus is restricted to the Red Sea and the Gulf of Aden, and it differs from the similar C. fasciatus in having modally fewer gill rakers on the first gill arch, a total of 13–16 (mean 13.9, usually 13 or 14 ) (vs. 13–16, mean 14.7, usually 14 or 15), in developing a ragged posterior margin of the caudal fin with age (versus only upper and lower caudal-fin lobes developing with age), and in its color pattern. The phylogenetic analysis of the COI barcoding region accords with the species status of C. quinquecinctus with the placement of the two sister species in two divergent and reciprocally monophyletic evolutionary lineages. A full description of C. quinquecinctus and diagnosis of C. fasciatus is provided here for comparison. In addition, the data include a table of the results of the meristic and morphological examination of type and additional specimens of both species from throughout their distribution ranges as well as a table of gill-raker counts of all examined specimens. Underwater color photographs are provided for comparison of juveniles, females and males of both species.